2022
DOI: 10.1111/maps.13904
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated neutron and X‐ray computed tomography of meteorites: Detection and distribution of hydrogen‐bearing materials

Abstract: The presence and distribution of hydrogen-bearing materials in meteorites are important constraints on processes in the early solar system, and the delivery of volatile constituents to growing planets. Here, we show that coordinated neutron and X-ray computed tomography, NXCT, can reveal the presence and distributions of hydrogenbearing materials in meteorites, and thus help constrain the presence and actions of water in the early solar system. NXCT is nearly nondestructive of meteorite samples. Neutron fluenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 104 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…In a recent study, Treiman et al. (2022) reported that their NCT study of a chondrite meteorite sample had a very limited effect (below uncertainty levels in the current analyses) on the isotopic systems of a set of isotopes, for example, Hf‐W, within the sample and that NCT caused negligible heating. However, they note that some high‐precision isotopic analyses could be affected and that both XCT and NCT will influence thermoluminescence and thus overprint the cosmic ray exposure records within meteorites (see Sears et al., 2016; Treiman et al., 2022).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In a recent study, Treiman et al. (2022) reported that their NCT study of a chondrite meteorite sample had a very limited effect (below uncertainty levels in the current analyses) on the isotopic systems of a set of isotopes, for example, Hf‐W, within the sample and that NCT caused negligible heating. However, they note that some high‐precision isotopic analyses could be affected and that both XCT and NCT will influence thermoluminescence and thus overprint the cosmic ray exposure records within meteorites (see Sears et al., 2016; Treiman et al., 2022).…”
Section: Discussionmentioning
confidence: 80%
“…(2022) reported that their NCT study of a chondrite meteorite sample had a very limited effect (below uncertainty levels in the current analyses) on the isotopic systems of a set of isotopes, for example, Hf‐W, within the sample and that NCT caused negligible heating. However, they note that some high‐precision isotopic analyses could be affected and that both XCT and NCT will influence thermoluminescence and thus overprint the cosmic ray exposure records within meteorites (see Sears et al., 2016; Treiman et al., 2022). Also, it remains unknown whether NCT has detectable effects on chemical structures (such as might be detectable by e.g., Raman spectroscopy) or on organic molecules of possible relevance in the search for organic markers of extraterrestrial life.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations